Exploring the Sources of Stress Among Public School Principals: A Comparative Study of Global and Indonesian Perspectives - Yosef Budiman; Yadi Suryadi; Johar Permana; Danny Meirawan (Pedagogia: Jurnal Ilmiah Pendidikan, 2024)
This study examines the sources of stress among public school principals in Bogor Regency, Indonesia. Using a qualitative approach, four principals from junior and senior high schools were interviewed. The findings indicate that significant stressors include interpersonal conflicts with senior teachers and parents, resource shortages especially financial constraints, and high demands from stakeholders for academic and non-academic achievements. Additional stressors specific to the Indonesian context are pressures from pseudo-journalists, the ambiguity of funding regulations, the implementation of the zoning system in student admissions, and mandatory performance evaluations. The study emphasizes the need for policy reforms to provide clearer guidelines, improve financial support, and offer conflict management training. Addressing these stressors is crucial for enhancing principal well-being and promoting effective school leadership. Future research should explore tailored solutions for these unique challenges in Indonesian public schools.